Comparative studies of two methods of weight loss on wrestlers physical function - Liu, Y.; Feng, L. (2008 International Convention on Science, Education and Medicine in Sport: Proceedings, Vol. III, 2008)
Introduction: Several methods of weight loss are used by wrestlers. For example,Greece-Roman Wrestlers combined slow weight loss and rapid weight loss method, and free Wrestlers adopt uniform weight loss method before competition. Therefore, this paper objectively shows the influences of weight loss method on wrestlers' physical functions. The findings will provide references and examples for coaches and athletes in choosing appropriate ways to reduce weight. Methods Eleven Greece-Roman wrestling athletes and 12 free Wrestlers who participated in the 10th National Games were subjects. Monitoring of the athletes' indexes such as body composition, immunity system, incretion system, energy metabolism and physical strength quality during the period of weight loss training before competition was conducted to proceed with comparative studies on the two groups of data. Results Both weight loss methods may reduce body weight effectively, and fat percentages are improved. However, slow weight loss may lead to a higher percentage of fat consumption. By way of combining slow weight loss and rapid weight loss, counting of leucocytes and immunoglobulin remain unchanged; in uniform weight loss method, there is no obvious change in the amount of leucocytes, while IgG and IgA of immunoglobulin after weight loss are clearly lowered than those before weight loss. In both methods of weight loss, serum testosterone levels of athletes are reduced, which is consistent with research results of Booth and Strauss. In this research, dropping range of serum testosterone by way of uniform weight loss is notably higher than that of combining low weight loss and rapid weight loss. When combining slow weight loss and rapid weight loss, there is no distinct change in blood BUN of athletes before and after weight loss; by way of uniform weight loss, athlete`s blood urea after weight loss is obviously higher than that before weight loss. When combining slow weight loss and rapid weight loss, grip power of athletes does not change much before and after weight loss; while by means of uniform weight loss, grip of athlete after weight loss is lower than that before weight loss. Conclusions Both methods of combining slow weight loss and rapid weight loss and uniform weight loss may reduce body weight of athletes. Nevertheless, the former is superior than the latter in improving body compositions. As for influences on immunity capabilities of athletes, the method of combining slow weight loss and rapid weight loss is less than that of uniform weight loss. For influences on the incretion system of athletes, the method of combining slow weight loss and rapid weight loss is less than that of uniform weight loss. With regards to energy consumption of athletes, the method of combining slow weight loss and rapid weight loss is less than that of uniform weight loss. With regard to influences on physical strength qualities of athletes, the method of combining slow weight loss and rapid weight loss is less than that of uniform weight loss.